Peran Moderasi Ukuran Perusahaan terhadap Hubungan Leverage dan Likuiditas terhadap Nilai Perusahaan - Arinka Febi Anjani; Indah Yuliana (Ekonomis: Journal of Economics and Business, 2023)
Firm value is used to determine how good a company is in the eyes of investors, while company size is used with the aim of determining how big or small a company is and to show the wealth of the company. This study aims to see whether the size of a company can provide moderation between the relationship of leverage and liquidity to the value of a company in the types of companies in the infrastructure sector, utilities and transportation, the consumer goods sector and the financial sector listed on the Indonesia Stock Exchange (IDX) in the 2017-2017 period. 2021. In this study, researchers used multiple linear regression test methods and moderation tests that applied Moderating Regression Analysis (MRA). The results of this study show that leverage proxied by DER has no negative effect and is not significant on firm value. Meanwhile, leverage which is poked with DAR affects firm value but not significantly. The liquidity proxied by CR does not significantly affect company value. Meanwhile, liquidity which is poked with QR gets the result that CR does not significantly affect firm value. For MRA, the results show that firm size can moderate the effect of DER on firm value and firm size cannot moderate the DAR relationship on firm value, firm size is able to moderate the effect of CR on firm value and firm size is able to moderate the QR relationship on firm value.